PERSEPSI MAHASISWA STIE MUHAMMADIYAH JAMBI TERHADAP KAHOOT SEBAGAI MEDIA PEMBELAJARAN BAHASA INGGRIS - Rahmat Fajar; Syilvia Wenni (Universitas Muhammadiyah Muara Bungo, 2019)
This study looks at the extent to which kahoot can be used by STIE Muhammadiyah Jambi students in understanding teaching materials as well as analyzing students' perceptions about the strengths and weaknesses of this media when it is practiced in daily teaching. The target of this research is the first year students of STIE Muhammadiyah Jambi. The research method used is quantitative descriptive. Data was taken from observations, field notes and questionnaires that were analyzed using qualitative data analysis. The results showed that the majority of respondents stated that Kahoot's main advantages were practical and easy to use. The majority of respondents did not experience obstacles to use this application. The biggest benefit felt by respondents is a pleasant learning atmosphere and sufficient results to show their ability to understand the material. In addition, the ability of lecturers is sufficient in the use of learning media. This can be seen from the level of participant satisfaction related to lecturer performance. Meanwhile, the biggest drawback of using Kahoot is network-related technical constraints and there is no opportunity to change answers. keywords: learning tool, students perceptions, effectiveness of kahoot